Exploring Fashion Purchase Intentions in Digital Marketplaces: TAM Perspectives Among UNY Students - Mahanani, Chytra; Jerusalem, Mohammad Adam (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2025)
Digital transformation has changed people's consumption patterns, especially in purchasing fashion products online. This study aims to explore the factors that influence the intention to buy fashion through the digital marketplace among students of the State University of Yogyakarta (UNY) using the Technology Acceptance Model (TAM) approach. This study uses a quantitative method with a survey design and Structural Equation Modeling (SEM) analysis techniques based on PLS. Data was collected through an online questionnaire of students using the marketplace. The results of the study show that perceived ease of use and perceived usefulness have a significant influence on students' attitudes and purchase intentions towards fashion products in the marketplace. In addition, external variables such as information quality and personalization have also been shown to influence the perception of convenience and usability. The developed research model successfully maps the relationships between variables significantly, which strengthens the validity of TAM in the context of digital purchases. These findings provide implications for MSME digital marketing strategies and the development of technology-based entrepreneurship curricula in higher education.